Prophylactic Anticonvulsants in Intracerebral Hemorrhage - Mackey, Jason (Neurocrit Care, 2017)
BACKGROUND AND PURPOSE: Prophylactic anticonvulsants are routinely prescribed in the acute setting for ICH patients, but some studies have reported an association with worse outcomes. We sought to characterize the prevalence and predictors of prophylactic anticonvulsant administration after ICH as well as guideline adherence. We also sought to determine if prophylactic anticonvulsants were independently associated with poor outcome. METHODS: We performed a retrospective study of primary ICH in our two academic centers. We used a propensity matching approach to make treated and non-treated groups comparable. We conducted multiple logistic regression analysis to identify independent predictors of prophylactic anticonvulsant initiation and its association with poor outcome as measured by modified Rankin score. RESULTS: We identified 610 patients with primary ICH, of whom 98 were started on prophylactic anticonvulsants. Levetiracetam (97%) was most commonly prescribed. Age (OR: 0.97, 95% CI: 0.95–0.99, p < .001), lobar location (OR: 2.94, 95% CI: 1.76–4.91, p < .001), higher initial NIHSS score (OR: 2.31, 95% CI: 1.40–3.79, p = .001), craniotomy (OR: 3.06, 95% CI: 1.51–6.20, p = .002) and prior ICH (OR: 2.36, 95% CI: 1.10–5.07, p = .028) were independently associated with prophylactic anticonvulsant initiation. Prophylactic anticonvulsant use was not associated with worse functional outcome (mRS 4–6) at hospital discharge or with increased case-fatality. There was no difference in prescribing patterns after 2010 guideline publication. DISCUSSION: Levetiracetam was routinely prescribed following ICH and was not associated with worse outcomes. Future investigations should examine the effect of prophylactic levetiracetam on cost and neuropsychological outcomes as well as the role of continuous EEG in identifying subclinical seizures.